P190 Non-GCA diagnoses from a GCA fast track clinic: a single centre with four years' experience (2016-2019). (20th April 2020) - kayani, Abdul; Sebastian, Alwin; Ranasinghe, Chavini; Whitlock, Madeline; Hussain, Hadi; Dasgupta, Bhaskar
Abstract: Background: Giant cell arteritis (GCA) has protean manifestations including temporal headache, visual disturbances, constitutional symptoms, jaw and tongue pain; symptoms which overlap with other conditions which mimic GCA. An important benefit of a fast-track clinic (FTC) is to rapidly exclude the diagnosis GCA to avoid inappropriate steroid exposure. We analysed data for patients referred with suspected GCA to our FTC where GCA diagnosis was subsequently excluded with fast-track ultrasound (US) and other investigations. Methods: This retrospective data was extracted from the GCA fast-track electronic referral system at Southend University Hospital from January 2016 to July 2019. Results: 1, 057 patients were seen at the fast-track clinic in this study period (Table 1). 690 (65.28%) were females. Only 15% (159) of the participants had a confirmed diagnosis of GCA (majority using US but also with other investigations such as biopsy or PET CT). Non-GCA patients accounted for 85% (898) and had a variety of differential diagnoses. In 222 (23.7%) no additional diagnosis was made after excluding GCA and patients were referred back for an expectant follow-up and assessment should any new features develop. In 204 (22.7%), polymyalgia rheumatica (PMR) was diagnosed with classical clinical symptoms and US of bilateral glenohumeral joints or response to a trial of low dose oral steroids. Another major group had different types of headaches 141 (15.71%) at presentation mimicking GCA. This included migraine 79 (56.0%), cervicogenic 58 (41.13%) and cluster headaches 4 (2.83%). Infectious causes were limited to head and neck infections 89 (9.91%) such as periorbital swelling, shingles and sinusitis. Neurological causes such as cervical spondylosis, cranial nerve palsy and TIA contributed to 7.9%. Chronic pain and other causes contributed 74 (8.24%) and 97 (10.8%) respectively. Other causes included medication-related (33), stress (21), cancer (4), RS3PE (4), glaucoma (2) and ANCA-associated vasculitis (33). Conclusion: An FTP clinic not only diagnoses GCA rapidly but is also able to rapidly screen non GCA and prevent unnecessary steroid treatment. It also requires a screening tool like GCA probability score to triage referrals to enable a more efficient service. Disclosures: A. kayani None. A. Sebastian None. C. Ranasinghe None. M. Whitlock None. H. Hussain None. B. Dasgupta Consultancies; Roche, Sanofi, GSK. Grants/research support; Roche.